2016
DOI: 10.14257/ijunesst.2016.9.4.24
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Economic Integration of BIMSTEC: Trade and Investment Scenario

Abstract: The purpose of this study is to explore the trade and investment potential under the ambit of regional cooperation comprising the seven contiguous countries of Bangladesh, India, Sri Lanka, Nepal, Bhutan, Thailand and Myanmar (BIMSTEC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…On the other hand, Neighboring India tops the list in terms of imports, which is why it has the most significant trade deficit with India (Table 4 & 5). Several researchers, including Newfarmer & Pierola (2007), Kim (2016), andNeena (2014), discovered less or more significant similar results, which corroborated the findings of the present study.…”
Section: As Seen Insupporting
confidence: 91%
“…On the other hand, Neighboring India tops the list in terms of imports, which is why it has the most significant trade deficit with India (Table 4 & 5). Several researchers, including Newfarmer & Pierola (2007), Kim (2016), andNeena (2014), discovered less or more significant similar results, which corroborated the findings of the present study.…”
Section: As Seen Insupporting
confidence: 91%
“…India’s Minister of External Affairs, Subrahmanyam Jaishankar, stated that BIMSTEC fits perfectly with India’s vision, as expressed in its ‘Neighborhood First’ and Act East policy. This statement reflects the importance attached to BIMSTEC by India (Rahman and Kim 2016 ). It also illustrates the common assumption that India is being driven by interests that are likely to establish India’s vision of increasing its geopolitical dominance and economic strength in the South Asian and Southeast Asian regions.…”
Section: Are India’s Ideas and Interests Compatible With Bimstec’s Su...mentioning
confidence: 76%
“…With an ambition to pursue mutual trade, connectivity, cultural, technical and economic development within South East Asia and South Asia region, in 1997, the Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation (BIMSTEC) was founded. Rahman and Kim (2016) reported that BIMSTEC countries have developed strategies and policies on several mutually agreed issues such as economic cooperation, social development and cultural exchange and aims towards harnessing the supremacy of emerging markets across the area. However, in this developing region, the magnitude of SE is larger along with the non-conducive political stability.…”
Section: Introductionmentioning
confidence: 99%